Compound traditional Chinese medicine dermatitis ointment ameliorates inflammatory responses and dysregulation of itch-related molecules in atopic dermatitis - Rongrong Zhang; Hongyin Zhang; Shuai Shao; Yingxin Shen; Fengqin Xiao; Jiaming Sun; Songlan Piao; Daqing Zhao; Guangzhe Li; Mingming Yan (BMC, 2022)
Abstract Background Atopic dermatitis (AD) is a chronic inflammatory skin disease accompanied with itchy and scaly rash. Compound traditional Chinese medicine dermatitis ointment (CTCMDO) consists of a mixture of extracts from five plants, which had been used in AD treatment due to good anti-inflammatory and anti-allergic effects. Materials and methods In this study, high-performance liquid chromatography (HPLC) and liquid chromatography/mass spectrometer (LC/MS) were performed to analyze the active ingredients of CTCMDO in detail and to establish its HPLC fingerprint. Furthermore, the anti-inflammatory and antipruritic activities of CTCMDO were studied in the treatment of DNCB-induced AD in mice. Results A total of 44 compounds including phenylpropionic acid compounds, alkaloid compounds, curcumin compounds and lignans were identified via combined HPLC and LC/MS. A fingerprint with 17 common peaks was established. In AD-like mice, DNCB-induced scratching behavior had been suppressed in the treatment of CTCMDO in a dose-dependent manner. Furthermore, the detailed experimental results indicated that the AD can be effectively improved via inhibiting the production of Th1/2 cytokines in serum, reversing the upregulation of substance P levels of itch-related genes in the skin, and suppressing the phosphorylation of JNK, ERK, and p38 in the skin. Conclusion This work indicated that CTCMDO can significantly improve AD via attenuating the pathological alterations of Th1/2 cytokines and itch-related mediators, as well as inhibiting the phosphorylation of mitogen-activated protein kinase (MAPK) and nuclear factor-kappa B (NF-κB).